THE IMPACT OF GOOGLE FORM PRACTICE TEST ON IMPROVING NON-ENGLISH STUDENTS’ TENSES - Kaloeti, Ade Kristianus (Universitas Muhammadiyah Metro, 2024)
Numerous studies have been conducted on Google Forms; however, there has yet to be research that explores the relationship between the impact of Google Forms and the development of tense proficiency among university students when learning the English language. The purpose of this research is to determine whether there is an impact on students' improvement of their mastery of tenses in English when given practice tests in the form of Google Forms. This research utilized an experimental quantitative method to observe the impact of practice tests in Google Forms after a pre-test and before a post-test. The study employed 35 undergraduate students majoring in Management at Immanuel Christian University. Initial data from the pre-test was collected before the exercises in Google Forms were given, and final data from the post-test was collected after the exercises in Google Forms were administered. These data were then tested for normality. Since the data did not have a normal distribution, they were tested using the Wilcoxon Signed-Rank Test. Additionally, the data were analyzed using the N-Gain score test. Based on the Wilcoxon Signed Rank test with a probability value less than 0.05, the effect of providing exercises in Google Forms on improving understanding tenses in English was seen. Furthermore, the N-Gain test results showed high scores and effective percentages, proving that the practice test method in Google Forms effectively enhances non-English major students' understanding of tenses in English. Consequently, English language instructors can implement the method of practice tests on Google Forms in their teaching. For future research, it can be investigated whether there is a significant difference in English tense mastery between students who receive practice tests on Google Forms and those who do not.